PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTELPURI SARON DENPASAR - Donna Meilia Indirawati; A.A. Ketut Sri Asih; Ni Putu Rizka Indrayanti (Journal Research of Management, 2021)
Every organization has human resources which are the most important assets for the company, where those human resources have the ability to develop in determining the company's success in the long run. Human resources in the company need to be managed with the demands and capabilities of the organization. The study aims to: 1) determine the effect of work motivation on employee performance, 2) determine the effect of job satisfaction on employee performance, 3) determine the effect of work motivation and job satisfaction on employee performance, 4) the independent variables that have a dominant influence on employee performance at Puri Hotel Saron Denpasar. The study population was all staff at the Puri Saron Hotel in Denpasar totaling 60 people. The analytical tool used is multiple linear regression analysis. Hypothesis testing used is a t-test tool to test the partial effect of work motivation and job satisfaction on employee performance, as well as analysis of determination to analyze the effect of independent variables on the dependent variable. The regression equation obtained: Y = 0.520 + 0.618 + 0.434 X2. This model shows that: 1) there is a positive and significant influence of work motivation on employee performance, 2) there is a positive and significant effect on job satisfaction on employee performance, 3) the amount of influence contributed by work motivation and job satisfaction on employee performance is 71.2% , and 4) work motivation is a variable that has a dominant influence on employee performance at the Puri Saron Hotel in Denpasar.